1967
DOI: 10.1104/pp.42.11.1612
|View full text |Cite
|
Sign up to set email alerts
|

Preparation of Radioactive Gibberellin A1 and its Metabolism in Dwarf Peas

Abstract: Summary. G(iberellin A1-3,4-3H was prepared by selective catalytic reduction of gibberellic acid with a mixture of tritium and hydrogen. 3H-GA1 was applied at physiological concentrations to dwarf peas and the metabolism of the horimone was investigated. tH-GA1 was converted to an acidic, biologically active compound. Radioactive but biologically inactive compounds were also found in the neutral fraction and could not be converted to

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
25
1

Year Published

1971
1971
1989
1989

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 63 publications
(27 citation statements)
references
References 13 publications
1
25
1
Order By: Relevance
“…Although conclusive identification was not made in our study, TLC and GLC evidence strongly suggested GA8 as a primary metabolite of GA1. This probable identification of GA8 suggests that the GA metabolic pathway in cucumber may be similar to that of other plant species (9,13,14,17). The conversion of GA4 to GA, by a single hydroxylation (4) seems relevant to cucumber as both GA, and GA4 occur in cucumber (7).…”
Section: Methodsmentioning
confidence: 98%
See 2 more Smart Citations
“…Although conclusive identification was not made in our study, TLC and GLC evidence strongly suggested GA8 as a primary metabolite of GA1. This probable identification of GA8 suggests that the GA metabolic pathway in cucumber may be similar to that of other plant species (9,13,14,17). The conversion of GA4 to GA, by a single hydroxylation (4) seems relevant to cucumber as both GA, and GA4 occur in cucumber (7).…”
Section: Methodsmentioning
confidence: 98%
“…The metabolism of 3H-GA1 in barley half seeds (14), peas (9), and beans (15,17) resulted primarily in the production of GA8 and GA8-glycoside. Although conclusive identification was not made in our study, TLC and GLC evidence strongly suggested GA8 as a primary metabolite of GA1.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…It should be noted that an increased growth rate is not necessarily associated with increased GA metabolism. For example, dwarf peas show marked differences in growth when kept in light or darkness, while metabolism of`H-GA1 was the same (10), and that of 'H-GA5 only slightly different (15) under the two conditions. If GAs are biologically active in the chemically unchanged form as shown for GA1 and GA, in peas (10,15), metabolism of GA per se will not contribute to growth.…”
Section: Gibberellins and Growth Inispinachmentioning
confidence: 99%
“…For example, dwarf peas show marked differences in growth when kept in light or darkness, while metabolism of`H-GA1 was the same (10), and that of 'H-GA5 only slightly different (15) under the two conditions. If GAs are biologically active in the chemically unchanged form as shown for GA1 and GA, in peas (10,15), metabolism of GA per se will not contribute to growth. However, more GA will be available to spinach plants under LD because of increased GA biosynthesis, and this, combined with the increased sensitivity to GA, could be responsible for increased petiole growth and stem elongation under LD.…”
Section: Gibberellins and Growth Inispinachmentioning
confidence: 99%